Packs : strength in numbers - Salyer, Hannah (Houghton Mifflin Harcourt, 2020)
"A full-color, exquisitely illustrated celebration of animals who live in packs, herds, pods, and more. Packs shows how togetherness and teamwork help many creatures thrive." -- amazon.com